Status Gizi Balita Masa Pandemi Covid-19 di Kabupaten Tapanuli Utara - Elly Sianturi; Sulastri Pakpahan (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The problem of under-five nutrition is one of the highest health problems in Indonesia with "three burdens of malnutrition" long before Covid-19. More than 2 million children are underweight toddlers. Although there is a tendency to decrease the malnutrition rate from 5.7% in 2013 to 3.9% in 2018, this figure is still quite high compared to countries in the ASEAN region. This situation has been exacerbated by the COVID-19 pandemic. The significant impact of Large-Scale Social Restrictions (PSBB) is related to the economic sector and all aspects of children's lives, both in terms of health, welfare, development and future of children. Based on the results of Riskesdas (2018), the proportion of very thin and thin children under five in Indonesia decreased significantly from 12.1 percent in 2013 to 10.2 percent in 2018, while the proportion of thin and very thin toddlers in North Tapanuli in 2017 was 10.1 percent. It takes hard work and maximum effort to maintain this achievement by regularly monitoring the nutritional status of toddlers so that they get immediate treatment and do not become chronic nutritional problems. This research method is an analytic survey with a cross sectional research design, aiming to determine the relationship between the independent variables, namely maternal education, family income, knowledge of parenting patterns, number of family members and food consumption, with the dependent variable being the nutritional status of toddlers Weight according to Height (BB/TB). Education is not related to the nutritional status of toddlers with p value 0.15 > 0.05, family income in this study is related to the nutritional status of toddlers where p value is 0.008 < 0.05, there is a relationship between mother's knowledge about parenting patterns and nutritional status of toddlers. The results of this study indicate that there is a relationship between mother's knowledge about parenting with p-value 0.015 <0.05. Those with low knowledge are 5.9 times more at risk of having under-fives with underweight nutritional status. The number of family members is not related to the nutritional status of children under five where the p value is 0.698 > 0.05. Food consumption is related to nutritional status where p value is 0.008 <0.05, multivariate test, where toddlers with a history of poor food consumption will be at risk 4.5 times compared to toddlers with a history of good food consumption. Family income, mother's knowledge, food consumption is related to the nutritional status of toddlers, education and the number of family members are not related to the nutritional status of under five years.